Balance in Teaching Balaghah at Pondok Modern Darussalam Gontor - Agung Nurcholis, Agung Nurcholis; Yoke Suryadarma; Rendi Sabana (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study examines the principles of balance in teaching Balaghah (Arabic rhetoric) at Pondok Modern Darussalam Gontor, analyzing how these principles are applied in the instruction of Arabic rhetorical sciences. The research is based on qualitative content analysis of curricula and teaching materials at the institution, focusing on four dimensions of balance: balance between academic, emotional, and spiritual aspects, balance between theory and practice, balance between individual and social development, and balance in assessment methods. The findings reveal that the Balaghah teaching approach at Pondok Modern Darussalam Gontor embodies these principles through an integrated approach that connects theoretical knowledge of rhetoric with its practical applications, balances the study of traditional texts with the use of modern methods, combines individual and collaborative learning, and integrates academic, emotional, and spiritual dimensions in the educational process. The study presents a theoretical framework for teaching Balaghah based on balance principles, contributing to the development of Arabic rhetoric teaching methods and enhancing their effectiveness in various educational contexts. تبحث هذه الدراسة في مبادئ التوازن في تعليم البلاغة في معهد دار السلام كونتور الحديث، وتحلل كيفية تطبيق هذه المبادئ في تدريس علوم البلاغة العربية. تعتمد الدراسة على تحليل محتوى المناهج الدراسية والمواد التعليمية في المعهد، مع التركيز على أربعة أبعاد للتوازن: التوازن بين الجوانب الأكاديمية والعاطفية والروحية، والتوازن بين النظرية والتطبيق، والتوازن بين التنمية الفردية والاجتماعية، والتوازن بين التقليد والابتكار، والتوازن في أساليب التقييم. تكشف النتائج أن منهج تعليم البلاغة في معهد دار السلام كونتور يجسد هذه المبادئ من خلال نهج متكامل يربط بين المعرفة النظرية للبلاغة وتطبيقاتها العملية، ويوازن بين دراسة النصوص التقليدية واستخدام الأساليب الحديثة، ويجمع بين التعلم الفردي والتعاوني، ويدمج الأبعاد الأكاديمية والعاطفية والروحية في عملية التعليم. تقدم الدراسة إطارًا نظريًا لتعليم البلاغة قائم على مبادئ التوازن، مما يسهم في تطوير أساليب تعليم البلاغة العربية وتعزيز فعاليتها في السياقات التعليمية المختلفة.